Defining readmissions among patients undergoing open reduction and internal fixation (ORIF) in claims database analyses. (2nd January 2020) - Chitnis, Abhishek S.; Nandwani, Piyush; Ruppenkamp, Jill; Vanderkarr, Mollie; Holy, Chantal E.
Abstract: Objective : To evaluate the impact of using different readmissions definitions among patients undergoing open reduction and internal fixation (ORIF) of the femur, tibia, and fibula in claims databases. Methods : Patients from the IBM MarketScan Research Commercial and Medicare Databases receiving inpatient ORIF between 1 January 2010 and 31 January 2017 (index) were identified. Readmissions within 90 days were calculated starting from the index day of discharge to 2 days after discharge. Readmission rates were also reported after accounting for records for rehabilitation, aftercare, or transfer using discharge status, provider type, and Diagnosis Related Group (DRG) codes. For patients with "transferred" as the index hospitalization discharge status, readmissions were calculated 2 days after discharge. Results : A total of 82, 692 patients with ORIF for femur, tibia or fibula were identified; mean (SD) age was 60.1 (23.1) years and nearly two-thirds were female (62.3%). For the index hospitalization, 41.6% patients had "transferred" as the discharge status. The readmission rate calculated from the same day as the discharge was 14.7%. Readmission rates calculated 1 and 2 days after index discharge were 8.5 and 7.7%. After accounting for rehabilitation, aftercare and transfer, the corrected readmission rate was 8.6%. Corrected readmission rates calculated 1 and 2 days after index discharge were 7.2 and 7.2%, respectively. The most common diagnosis associated with same day readmission was rehabilitation, whereas that was not observed with readmissions 1 and 2 days after discharge. Conclusions : The accuracy of identifying true admissions was improved by defining readmissions as occurring after the day of discharge and by accounting for rehabilitation, aftercare, and transfer.